Poet in an Islamic Community: Cultural and Social Activities of Acep Zamzam Noor in Tasikmalaya, West Java - Moriyama, Mikihiro (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2015)
This article brings out the significance of social leader in the time of socio-political change in Indonesia since Soeharto left office in 1998 by describing and analyzing the projects and writings including poems of Acep Zamzam Noor (born in 1960), an activist and poet based in the Pesantren Cipasung (Cipasung Islamic school complex) in Tasikmalaya, West Java. He is respected not by his Islamic knowledge based on learning books, rather by his faith to God and deed based on his own experience. Acep’s oppositional stance in relation to political and religious authorities is manifest in various public projects including political parody and cultural activities in the local community. These respective projects constituted bases for the respect and support from which the institution of the social leader derives its significance in Islamic communities in Indonesia. This article adds to the literature by describing and analyzing an important stand of religious authority.DOI: 10.15408/sdi.v22i2.1920